THE RELATIONSHIP BETWEEN PERFORMANCE AND BENEFITS OF AGRICULTURAL COOPERATIVE TOWARD FARMERS’ ECONOMY AND BEHAVIOUR IN THE DISTRICT OF KOLAKA - Ilma Sarimutaqiyma Rianse; Usman Rianse; Slamet Hartono; Any Suryantini; Wa Kuasa (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
This study aimed to determine: (1) an analysis of the cooperative’s performance based on the  agricultural  criteria  in  the district  of Kolaka, according to  the guidelines  on cooperative fostering and  cooperative  classification;  (2)  the performance of  the cooperative  as perceived by  farmers  and  cooperatives management;  (3) determine  the benefits gained by farmers as members of cooperatives; (4) an analysis of the relationship between performance and the benefits obtained by farmers as a cooperative member. The results showed that,  based on the  Guidelines  for  Cooperatives  Classification,  the performance of agricultural cooperatives in Kolaka in 2007 was on the average of 61.58 and fell within the “quite well” category. In 2008 the average performance of 62.05 and cooperatives are included in the category quite well. In2009, the average performance of the cooperatives was  62.38, remaining in the same  category.  In 2010  the  average performance was 61.28, also staying  in the category of “quite well”. Furthermore,  the management of cooperatives as well as the majority of stakeholders considered that the agricultural cooperatives in Kolaka met the criteria of “quite well”, as many as 48.75%. The majority of  respondents  (65%) considered the agricultural cooperatives  in Kolaka helpful.  Based on  SEM  analysis,  the relationship  of  the agricultural  cooperative performance was found  to be positively correlated  to the benefits obtained by farmers. Standardized  coefficient  value  of 0.85  has a value  of  14.40t statistic.  Standardized coefficient value of 0.85 indicates that the performance and benefits of the cooperative have  a real  relationship  closeness.  Sequentially  the  components  of  performance  that contribute  from  the  largest to  the smallest are, firstly, the concern for the community, which is equal to0.86. The component of voluntary and open membership component is 0.80.  The component of  democratic  control  by members  is 0.79.  The component of economic participation of member is 0.71. And the component of education and training is  0.25.  Regarding the  components of  the  cooperative  benefits,  the components that contributes  sequentially,  from  the  largest to  the smallest, are  the economic benefits of marketing,  that is equal to 0.96;the benefits of a large savings and loan with 0.88;  the economic benefits of farmers needs 0.86; and social benefits 0.48.